MASCOT’s in situ analysis of asteroid Ryugu in the context of regolith samples and remote sensing data returned by Hayabusa2 - Katharina Otto; Tra-Mi Ho; Stephan Ulamec; Jean-Pierre Bibring; Jens Biele; Matthias Grott; Maximilian Hamm; David Hercik; Ralf Jaumann; Masahiko Sato; Stefan E. Schröder; Satoshi Tanaka; et al. (Earth, Planets and Space, 2023)
Abstract The Hayabusa2 mission provided a unique data set of asteroid Ryugu that covers a wide range of spatial scale from the orbiter remote sensing instruments to the returned samples. The MASCOT lander that was delivered onto the surface of Ryugu aimed to provide context for these data sets by producing in situ data collected by a camera (MasCam), a radiometer (MARA), a magnetometer (MasMag) and a spectrometer (MicrOmega). In this work, we evaluate the success of MASCOT as an integrated lander to bridge the gap between orbiter and returned sample analysis. We find that MASCOT’s measurements and derivatives thereof, including the rock morphology, colour in the visible wavelengths, possible meteorite analogue, density, and porosity of the rock at the landing site are in good agreement with those of the orbiter and the returned samples. However, it also provides information on the spatial scale (sub-millimetres to centimetres) at which some physical properties such as the thermal inertia and reflectance undergo scale-dependent changes. Some of the in situ observations such as the presence of clast/inclusions in rocks and the absence of fine particles at the landing site was uniquely identified by MASCOT. Thus, we conclude that the delivery of an in situ instrument like MASCOT provides a valuable data set that complements and provides context for remote sensing and returned sample analyses. Graphical Abstract